METODE STATE SPACE DALAM MERAMALKAN JUMLAH PENUMPANG KERETA API DI PULAU JAWA - SARASWITA, FITRI ANANDA DITA; SUMARJAYA, I WAYAN; HARINI, LUH PUTU IDA (E-Jurnal Matematika, 2020)
State space is an approach to model and predict together several time series data that are interconnected, and these variables have dynamic interactions. The purpose of this research is to model the number of train passengers in Java and find out the forecasting results using the state space method. The algorithm used to solve the state space model is the Kalman filter. In this research , a suitable final model is local level model with seasonal and produces MAPE value of 2% , this shows that the state space method is very accurately.